(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article examines various systems of presumption (consent or dissent) for post-mortem donation in European countries, specifically their impact on the development of transplantology within each country. For the purposes of this study, 24 countries were analyzed, of which 14 countries have a legal procedure for consent (Austria, Belgium, Bulgaria, UK, Spain, Italy, Netherlands, Norway, Poland, Portugal, Croatia, Hungary, France, Czech Republic) and 10 countries have a dissent procedure (Bosnia and Herzegovina, Greece, Estonia, Ireland, Latvia, Lithuania, Germany, Slovenia, Ukraine, Switzerland) for post-mortem donation. The study calculates the percentage of people awaiting organ transplantation relative to the population in each country. The findings of the study contribute significantly to improving the functioning of the legal system in the field of transplantology. According to the analysis, 2 comparative diagrams were created, graphically depicting the numerical data of this study.